2020
DOI: 10.1159/000509105
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: An Independent Predictor of Morbidity and Graft Loss after Kidney Transplantation

Abstract: Background: There is conflicting information on current medical and surgical complications associated with high body mass index (BMI) after kidney transplantation. Methods: In a single-center observational study, we analyzed the 5-year outcomes of all consecutive primary kidney transplant recipients between 2010 and 2015 based on BMI at the time of transplant. Results: There were 1,467 patients included in this study, distributed in the following groups based on BMI: underweight (n = 32, 2.2%), normal (n = 407… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Weight gain after transplantation is very common (81,104), and a significant increase in weight after transplantation has been associated with decreased patient survival (81). Obesity has also been associated with an increased risk of cardiac events and congestive heart failure after transplantation (105), as well as with the development of diabetes mellitus (106,107). Although there is conflicting data regarding the impact of obesity on kidney transplantation, it undoubtedly represents a risk factor for surgical complications, and it probably has a real impact on outcomes.…”
Section: Impact Of Obesity Before and After Kidney Transplantationmentioning
confidence: 99%
“…Weight gain after transplantation is very common (81,104), and a significant increase in weight after transplantation has been associated with decreased patient survival (81). Obesity has also been associated with an increased risk of cardiac events and congestive heart failure after transplantation (105), as well as with the development of diabetes mellitus (106,107). Although there is conflicting data regarding the impact of obesity on kidney transplantation, it undoubtedly represents a risk factor for surgical complications, and it probably has a real impact on outcomes.…”
Section: Impact Of Obesity Before and After Kidney Transplantationmentioning
confidence: 99%
“…Three of the 4 meta-analyses show a higher risk of DGF in BMI ≥30 kg/m 2 with different RR depending on the study: RR of 1.41 [36] or RR of 1.52 [37] or OR of 1.76 [38]. More recently, large population studies have reported similar results [42,43].…”
Section: Pharmacological Treatmentmentioning
confidence: 91%
“…They found a higher prevalence of wound infections and dehiscence (RR 3.13 [CI, 2.08-4.71; p < 0.001] and RR 4.85 [CI, 3.25-7.25; p < 0.001], respectively), incisional hernia (RR 2.72; CI, 1.05-7.06; p = 0.04), and a higher hospital length (2.31 days; CI, 0.93-3.69; p = 0.001) in obese population. Aziz et al [42] found that wound complications were associated with an increased length of hospitalization and a higher risk for rehospitalization.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…In an analysis from the USRDS including 7521 patients, Glanton et al [ 56 ] compared the mortality rates among transplant recipients and patients on hemodialysis with class I, II and III obesity and found that kidney transplantation from both deceased (HR 0.39, 95%CI: 0.33-0.47) and living donors (HR 0.23, 95%CI: 0.16-0.34) was associated with significant lower mortality rate of those who stayed on dialysis waiting for a kidney. Interestingly, the beneficial effect of transplantation was lost in the subgroup analysis of patients with class III obesity[ 57 ]. The beneficial effect of kidney transplantation among obese patients was recently confirmed by Gill et al [ 20 ], who analyzed a large cohort from the US renal registry and reported a 66% reduction in the risk of death in all BMI groups for patients receiving a living donor kidney, whereas among the deceased donor recipients, the reduction in the risk of death was 66% in patients with class I and II obesity and 48%in patients with class III obesity[ 20 ].…”
Section: Obesity and Kidney Transplantationmentioning
confidence: 99%
“…Moreover, obese transplant recipients have an increased risk of delayed graft function, probably as a consequence of a longer operative time, a prolonged hospital stay, an increased rate of acute rejection, an increased rate of new-onset DM and hospital readmission[ 6 , 18 , 57 , 68 - 70 ].…”
Section: Obesity and Kidney Transplantationmentioning
confidence: 99%